From the margins to the mainstream : the Domestic Violence Services Movement in Victoria, Australia, 1974-2016 - Theobald, Jacqui; Murray, Suellen; Smart, Judith, 1950- (Melbourne University Publishing, 2017)
In the aftermath of the 2015 Victorian royal commission, billions of dollars of government funds have been committed to improving responses to women and children experiencing domestic violence. Such attention was unimaginable forty years ago when feminists in Victoria and across Australia first established women's refuges. At that time, domestic violence was not publicly acknowledged or tackled in any coherent way at a Commonwealth or state government policy level. While services that provided accommodation to women and children in crisis had certainly existed for a long time, the refuge movement of the 1970s made explicit the link between domestic violence and the need for refuge, framing domestic violence as a manifestation of gender inequality and an imbalance of power between men and women. This book illuminates how the women's domestic violence services movement in Victoria emerged, how members organised amidst diversity and worked towards achieving their goals, made sense of their experiences and dealt with the obstacles they encountered while undertaking action to create significant change for women.